A comparative study of dry sliding wear behaviour of sillimanite and rutile reinforced LM27 aluminium alloy composites. (6th January 2020) - Gupta, Rahul; Sharma, Sandeep; Nanda, Tarun; Pandey, O P
Abstract: The present work compares the dry sliding wear characteristics of sillimanite reinforced and rutile reinforced LM27 aluminium alloy based composites prepared by stir casting process. Particles in the size range of 1–32 μ m were added in 5, 10, and 15 wt%. Microstructure, nanohardness, coefficient of friction, and wear rate characteristics were evaluated. Optical microscopy revealed uniform distribution of both sillimanite and rutile particles in the matrix. The hardness of sillimanite reinforced composites was higher than rutile reinforced composites. Further, the wear resistance of sillimanite reinforced composites was superior to rutile reinforced composites. However, coefficient of friction values of sillimanite particle reinforced composites were higher than the rutile particle reinforced composites. SEM-EDS analysis of wear track and wear debris revealed that abrasive wear and adhesion/delamination mechanisms were responsible for the wear of composites at low and high applied load conditions respectively.